Entrenching child rights protection in Nigeria: the problem of constitution and culture - Ogunde, Oluwafifehan O. (2018)
The thesis examines child rights protection in Nigeria particularly in the context of problems created by the constitution and culture in establishing an effective child rights framework. Its central argument is that the peculiar constitutional arrangement hinders the effective implementation of the Nigerian Child Rights Act (CRA) 2003. It also argues that cultural perceptions with respect to children also serve as formidable opposition to the recognition of children as rights holders. Having argued along these lines, the thesis proposes certain reform measures that may be adopted in resolving the problems created by these factors and assesses their suitability to the Nigerian society.